MESOPOROUS Cu-DOPED TiO2 SUBMICRON PARTICLES FOR SOLAR-LIGHT ASSISTED DEGRADATION OF MODEL DYE POLLUTANT - Rsaldina, Dana (Nazarbayev University School of Sciences and Humanities, 2021)
Titanium dioxide (TiO2) is a widely used material in different industries due to its long-term photostability, economic benefits, and ability to oxidize different types of organics. However, bare TiO2 has photocatalytic activity limitation due to wide bandgap - 3.2 eV, hence, it absorbs only in the UV region. Therefore, it is necessary to decrease the bandgap of the TiO2 photocatalyst to increase its’ absorbance. The most promising methods can be considered doping and surface area enlargement. In this thesis, we prepared porous Cu-doped TiO2 particles using a solvothermal method. The photodegradation efficiency of Cu-TiO2 particles was tested by using Rhodamine B (RhB) dye pollutant and compared to a commercial P25 photocatalyst. The prepared photocatalyst has a size of 100-164 nm that is suitable for collecting and reusability in contrast to P25 (21 nm). As the result of the lower bandgap (2.9 eV) and large surface area (~110.45 m2/g), the degradation rate of RhB in the presence of the Cu-TiO2 (k=0.296/min) was ~10.4% and ~ 114.5% higher compared to P25 (k=0.268/min) and pure H2O2 (0.138/min), respectively. Overall, the main novelties of the prepared photocatalyst are their larger size that could be useful for the reusability and mesoporous structure that positively influence on photocatalytic activity
Keywords: Titanium dioxide; Type of access: Gated Access